Вдосконалення навчально-методичного забезпечення дисциплін «Комп’ютерно-інтеґровані технології» та «Основи релейного захисту» на кафедрі «Електроенергетика і автоматизація» - Лобода, Олександр Іванович; Лобода, Александр Иванович; Loboda, Oleksandr; Кашкарьов, Антон Олександрович; Кашкарев, Антон Александрович; Kashkarov, Anton; Сілі, Іван Іванович; Сили, Иван Иванович; Sili, Ivan (Мелітополь: ТДАТУ, 2019)
UK: У статті розглянуто основні етапи організації методичної роботи на кафедрі «Електроенергетика і автоматизація» ТДАТУ, вдосконалення навчально-методичного забезпечення дисциплін та приведено практичні результати впровадження рекомендацій в навчальний процес. EN: The article deals with the main organization stages for methodical work at the Department of Power Engineering and Automation TSATU, improvements of teaching and methodological implementation for disciplines and shows implement of practical results in the educational process.
Improvements for educational and methodological implementation of disciplines "Computer-integrated technologies" and "The basics of relay protection" in the Department of Power Engineering and Automation TSATU
Keywords: навчальний процес; самостійна робота; експериментальний стенд; струмове реле; лабораторна робота; Trace Mode; Texнo- FDB; educational process; independent work; experimental stand; current relay; laboratory work; Texno-FDB